Impact of Sequence Parameters in the Frequency Domain: Utilizing Physically Consistent Line Parameters - Guevara, Jesus E.; Colqui, Jaimis S. L.; Kurokawa, Sergio [UNESP]; Filho, José Pissolato (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper investigates the impact of sequence parameters over a wide frequency range of an overhead transmission line when it considers the calculation of parameters of the line physically more consistent and soil properties that vary with frequency. For this purpose, it is calculated to the ground-return impedance and admittance of the transmission line using Petterson's approach, which employs a more rigorous voltage formulation. Additionally, in this calculation, soil properties were included using the frequency-dependent soil model. For comparison, the results from the ATP program, which employs in the calculation of parameters of the line Carson's approach, were used; this approach considers the less rigorous voltage formulation, assumes ideal ground conditions for ground-return impedance and admittance calculations, and does not consider frequency-dependent soil parameters. The results demonstrate that using physically more consistent line parameters and frequency-dependent soil parameters leads to significant differences in several parameters of homopolar and non-homopolar sequences. These significant differences are particularly notable in homopolar and non-homopolar resistances, homopolar inductance, homopolar capacitance, homopolar propagation velocity, and homopolar and non-homopolar attenuation constants.
Keywords: earth-return impedance; frequency-dependent soil parameters; homopolar mode; non-homopolar mode; Overhead transmission line; sequence parameters